1999
DOI: 10.1080/014608699265356
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Affectionate Behaviors Adolescent Mothers Display Toward Their Infants in Neonatal Intensive Care

Abstract: This paper describes two studies that had three purposes: (a) to modify a parent-child interaction tool used previously in a neonatal intensive care unit (NICU); (b) to demonstrate interrater reliability, Chronbach's Alpha reliability, and construct validity of the tool with adolescent mothers, and (c) to determine the ability of nurses engaged in usual work duties to observe maternal behaviors. The first study tested interrater reliability. Two NICU nurses were trained, observed adolescent mothers (n = 20) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Christopher et al [27] used the Affectionate Behavior Assessment tool to assess maternal caring behaviors such as noninstrumental touch, looking at baby, and vocalization to the infant. The authors observed that young mothers who visited their babies less frequently exhibited less affectionate behaviors toward their infants compared with older mothers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Christopher et al [27] used the Affectionate Behavior Assessment tool to assess maternal caring behaviors such as noninstrumental touch, looking at baby, and vocalization to the infant. The authors observed that young mothers who visited their babies less frequently exhibited less affectionate behaviors toward their infants compared with older mothers.…”
Section: Resultsmentioning
confidence: 99%
“…This could be attributed to differing conceptions of adolescence cross-culturally [61]. A significant number of the studies also exclude parents of infants with congenital abnormalities and/or critical illness [16,27,31,36,59]. Such variation in selection criteria limits comparability of studies and understanding of adolescent parenting in varying circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation